Children Using Cochlear Implants Capitalize on Acoustical Hearing for Music Perception - Hopyan, Talar; Peretz, Isabelle; Chan, Lisa P.; Papsin, Blake C.; Gordon, Karen A. (Frontiers in Psychology, 2012)
Cochlear implants (CIs) electrically stimulate the auditory nerve providing children who are deaf with access to speech and music. Because of device limitations, it was hypothesized that children using CIs develop abnormal perception of musical cues. Perception of pitch and rhythm as well as memory for music was measured by the children’s version of the Montreal Battery of Amusia (MBEA) in 23 unilateral CI users and 22 age-matched children with normal hearing. Children with CIs were less accurate than their normal hearing peers (p<0.05). CI users were best able to discern rhythm changes (p < .01) and to remember musical pieces (p < .01). Contrary to expectations, abilities to hear cues in music improved as the age at implantation increased (p < .01). Further analyses revealed that this was because the children implanted at older ages also had better low frequency hearing prior to cochlear implantation and were able to use this hearing prior to cochlear implantation by wearing hearing aids. Access to early acoustical hearing in the lower frequency ranges appears to establish a base for music perception, which can be accessed with later electrical CI hearing.